High systemic bone mineral density increases the risk of incident knee OA and joint space narrowing, but not radiographic progression of existing knee OA: the MOST study. Issue 01 (15th January 2009) - Nevitt, M C; Zhang, Y; Javaid, M K; Neogi, T; Curtis, J R; Niu, J; McCulloch, C E; Segal, N A; Felson, D T
Abstract : Objectives: Previous studies suggest that high systemic bone mineral density (BMD) is associated with incident knee osteoarthritis (OA) defined by osteophytes but not with joint space narrowing (JSN), and are inconsistent regarding BMD and progression of existing OA. The association of BMD with incident and progressive tibiofemoral OA was tested in a large prospective study of men and women aged 50–79 years with or at risk for knee OA. Methods: Baseline and 30-month weight-bearing posteroanterior and lateral knee radiographs were scored for Kellgren-Lawrence (K-L) grade, JSN and osteophytes. Incident OA was defined as the development of K-L grade ⩾2 at follow-up. All knees were classified for increases in grade of JSN and osteophytes from baseline. The association of gender-specific quartiles of baseline BMD with risk of incident and progressive OA was analysed using logistic regression, adjusting for covariates. Results: The mean (SD) age of 1754 subjects was 63.2 (7.8) years and body mass index was 29.9 (5.4) kg/m 2 . In knees without baseline OA, higher femoral neck and whole body BMD were associated with an increased risk of incident OA and increases in grade of JSN and osteophytes (p<0.01 for trends); adjusted odds were 2.3–2.9-fold greater in the highest compared with the lowest BMD quartiles. In knees with existing OA, progression was not significantly related to BMD. Conclusions: In knees without OA, higher systemic BMD was associated with a greater risk of the onset of JSN and K-L grade ⩾2. The role of systemic BMD in early knee OA pathogenesis warrants further investigation.